Essential oils from Artemisia species inhibit biofilm formation and the virulence of Escherichia coli EPEC 2348/69. Issue 2 (6th February 2021) - Mathlouthi, Ahmed; Saadaoui, Nabil; Ben-Attia, Mossadok
Abstract: Enteropathogenic Escherichia coli E2346/69 (EPEC) has caused foodborne outbreaks worldwide and the bacterium forms antimicrobial-tolerant biofilms. The anti-biofilm formation of various components of essential oils extracted from selected medicinal plants were investigated and tested on EPEC and wild strains of E. coli . Oils extracted from the family Asteraceae and their major common constituents at 0.031 and 0.062% (V/v) were found to significantly inhibit biofilm formation without affecting the growth of planktonic cells. In addition, three plants belonging to this family ( Artemisia herba alba, Artemisia campestris and Artemisia absinthium ) played important roles in the antimicrobial activity. Interestingly, their essential oils reduced the ability of E . coli (the EPEC and K12 strains) to form a biofilm. The crystal violet reduction assay showed that the plant extracts tested reduced biofilm formation with the inhibition of bacterial attachment up to 45% for EPEC and 70% for E. coli K-12 after 24 h treatment at 0.62 mg ml −1, demonstrating that Artemisia oils had a high anti-biofilm activity on the bacteria tested. The results indicate that the locus of enterocyte effacement (LEE) acquired by horizontal transfer promotes the formation of the attaching and effacing (A/E) lesion and increases the capacity of the photogen strain (EPEC) to form a biofilm. The chemical composition of the volatile compounds was obtained by gas chromatography-mass spectrometry analysis, which showed that the essential oils consisted of thirty-four compounds. Chamazulene (39.21%), β-pinene (32.07%), and α-thujone (29.39%) were the main constituents of the essential oils of A. herba alba, A. absinthium and A. campestris, respectively.